PENGARUH PENERAPAN GAME KAHOOT DALAM MENINGKATKAN HASIL BEALAJAR PADA MATA PELAJARAN DESAIN GRAFIS KELAS X DI SMKT SOMAOPU - Dasmayanti Lestari; Abdul Muis Mapalotteng; Ruslan (UNM Journal of Technology and Vocational, 2023)
This research is a quasi-experimental or quasi-experimental research with the aim of 1. Knowing the application of the kahoot game 2. Knowing whether there is an effect of implementing the Kahoot Game in Improving Learning Outcomes in Class X Graphic Design Subject at SMKT Sombaopu 3. Knowing student responses to the kahoot game. This study consisted of two variables, namely the Kahoot Game media as the independent variable and student learning outcomes as the dependent variable, using the Pretest and Posttest Control Group Design research designs. The population in this study were all students of class X TKJ consisting of 2 classes with a total of 34. The research sample was class X TKJ 1 as a control class with 17 students and X TKJ 2 as an experimental class with 17 students selected through Simple Random. sampling. The data obtained were analyzed with descriptive statistics and inferential statistics. The results of the descriptive statistical analysis show that in the experimental class with the Kahoot Game learning media, the average pretest and posttest were 74.35 and the pretest was 74.35, while the learning using the lecture method obtained the average pretest was 34.59 and the posttest was 57.18, while the control class students' mastery was 6. % and 82% experimental class. The average result of the n-gain test for the experimental class was 0.46 and that for the control class was 0.3. The average effectiveness of the control class was 33.62 and the experimental class was 46.88. The results of inferential statistical testing with the Independent Samples T-Test obtained a significance value for the pretest and posttest p = 0.000 <α = 0.05. This means that H0 is rejected and H1 is accepted, thus the kahoot game learning media influences student learning outcomes in Class X Graphic Design Subject at SMKT Sombaopu. Student response test as many as 34 people get a score of 4.30 with a presentation of 86.14% in a very interesting category.